22 Coping with Medicines After Hospital Discharge; the Invisible Work of Older Patients and Their Care-Givers. (16th March 2021) - Tomlinson, J; Smith, H; Silcock, J; Karban, K; Fylan, B
Abstract: Introduction: Older patients often experience medication-related problems following discharge from hospital. These can be categorised as issues with obtaining medication, taking medication, medication effects or problems with communication or care co-ordination (Nicosia et al., Journal of General Internal Medicine, 2019, https://doi.org/10.1007/s11606-019-05463-z ). The aim of this study was to explore older adults' experiences of post-discharge medicines management, including the strategies they use to safely manage their changed medicines. Methods: Following ethical approval, patients aged 75 and above, with a change in their long term medicines, were recruited during admission to one of two hospitals in Yorkshire. Semi-structured interviews took place with the participants in their own homes, approximately two weeks after discharge. Interviews were audio recorded and transcribed. Data were analysed using the Framework method. Results: Twenty-seven patients (mean age 85 years; 6 males) consented to be interviewed. They described multiple self-management and safety strategies used to support medicines management in the early post-discharge phase. The work done included adaptations (to routines, the home environment and action plans), scaffolding (where patients and their care-givers support the primary care system by providing additional documentation or prompts to ensure medicines were supplied on time and were correct) and error avoidance (seeking information, performing checks and balances). Conclusion: Older patients experience gaps in their post-discharge medicines-related care which they had to bridge through implementing their own strategies or by enlisting support from others. This study shines a spotlight on to the invisible work that patients have to do in order to make post-discharge medicines management fit for purpose. Further work should consider those patients who are not able to carry out these tasks or who do not have any care-givers available for support and how this potential gap in care can be addressed.